2023
DOI: 10.1111/mmi.15135
|View full text |Cite
|
Sign up to set email alerts
|

Expansion microscopy of apicomplexan parasites

Abstract: Apicomplexan parasites comprise significant pathogens of humans, livestock and wildlife, but also represent a diverse group of eukaryotes with interesting and unique cell biology. The study of cell biology in apicomplexan parasites is complicated by their small size, and historically this has required the application of cutting‐edge microscopy techniques to investigate fundamental processes like mitosis or cell division in these organisms. Recently, a technique called expansion microscopy has been developed, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 127 publications
2
12
0
Order By: Relevance
“…By expanding biological samples in a hydrogel, Expansion Microscopy (ExM) has enabled the visualization of structural details much smaller than the resolution limit of conventional light microscopy [36][37][38][39][40]. The ExM method [38] has been applied in investigating subcellular details of apicomplexans (reviewed in [41]). Here we use a slightly modified version of this method to determine the arrangement of tubulin containing structures in developing daughters.…”
Section: Resultsmentioning
confidence: 99%
“…By expanding biological samples in a hydrogel, Expansion Microscopy (ExM) has enabled the visualization of structural details much smaller than the resolution limit of conventional light microscopy [36][37][38][39][40]. The ExM method [38] has been applied in investigating subcellular details of apicomplexans (reviewed in [41]). Here we use a slightly modified version of this method to determine the arrangement of tubulin containing structures in developing daughters.…”
Section: Resultsmentioning
confidence: 99%
“…Rhoptry biogenesis remains a poorly understood process, primarily due to the small size of P. falciparum ’s rhoptries, which, coupled with the limited resolution offered by conventional microscopy, has made their study challenging. Recent advances in microscopy techniques, such as UExM, have opened new possibilities for exploring these micron-sized secretory organelles (Liffner and Absalon 2023). Using UExM, we observed that RON11 is required for the proper biogenesis of rhoptry pairs, as its absence led to merozoites with single rhoptries, an unprecedented phenotype that has not been observed in any other apicomplexan system.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly for its use in single-celled organisms, U-ExM results in near-native preservation of cellular ultrastructure and 4 to 4.5-fold isotropic expansion 4 . U-ExM has been widely adopted in the study of the cell biology of apicomplexan parasites 13 .…”
Section: Introductionmentioning
confidence: 99%
“…U-ExM has been widely adopted in the study of the cell biology of apicomplexan parasites 13 . Apicomplexa are a phylum of largely parasitic single-celled organisms that include significant causes ofdisease in humans and livestock, such as malaria, toxoplasmosis and cryptosporidiosis.…”
Section: Introductionmentioning
confidence: 99%